Influence of time on the success of speaker identification - Dobrić, Arnalda (Array, 2003)
The aim of this work was to determine how accurately and reliably individuals can remember and identify speakers, and how that ability is influenced by the time lapsed between the first exposure to the voice and the time of testing. First presentation (30 &#8211 ; 40 s) included four speakers (two male, two female). Three-second segments of the original three and additional three speakers (three male, three female) were presented to listeners five minutes after the first exposure and (depending on which group the listeners were assigned to) one week, two weeks, four weeks and six weeks later. The subjects' task was to answer whether the speakers were among those four they heard the first time. The results reveal low reliability of listeners&#8217 ; responses in general, and significant effect of time on the success of speaker identification.